Effect of Naira/Us Dollar exchange rate volatility on the performance of the stocks market in Nigeria - Shettima, Mustapha; Abdussalam, Yusuf; Olayinka, Aminu Abdulrahim (Annals of Management and Organization Research, 2023)
Purpose: This study investigates the influence of various macroeconomic factors, including the exchange rate, interest rate, inflation rate, and Gross Domestic Product, on the performance of the Nigerian Stock Exchange NSE 100 index. Utilizing a decade of annual data spanning from 2011 to 2021, this research employs the Augmented Dickey-Fuller test to explore the impact of these macroeconomic variables on stock market performance. Research methodology: Within this context, the time series Autoregressive Distributed Lag (ARDL) model is employed to discern the ramifications of naira/US dollar exchange rate volatility on Nigeria’s stock market performance. Results: Multiple regression analysis results indicate a significant negative effect of the exchange rate on share returns, revealing that a 10% increase in the real exchange rate correlates with a 0.15% decrease in the ASPI. Similarly, the inflation rate is associated with a negative coefficient, suggesting an adverse effect on stock prices. In contrast, interest rates and GDP exhibit positive coefficients, with 5% and 10% impacts on the ASPI, respectively. Limitation: All data used in this study were secondary. However, data from previous years were not readily available. This is the main limitation of this study. Contribution: Ultimately, this study underscores the importance of forecasting the exchange rate as a pivotal determinant of business success, offering recommendations for future endeavors.